Contribution to a reflection on the functions of the Judge in Africa French-speaking region, based on the litigation of individual labor disputes. - (:unkn) unknown (My University, 2020)
The thesis deals with the question of the Judge / a permanent that is an important actor in the construction of the rule of law in African countries which have French as an official language. It is a question of understanding his real function from the method of recruitment, training (initial and continuous), the exercise of functions, especially when he intervenes in the litigation of individual labor disputes. The thesis also devotes a large part to the question of the independence of the Judge in all its forms but also to the revaluation of the function of the Judge from the index salaries to which he is entitled to exercise his functions well.
Keywords: African Research